Increasing the Reuse of Protein Non-Naïve Nonhuman Primates in Pharmaceutical Drug Discovery and Development: An Overview and Industry Position on the Challenges and Benefits. (August 2022) - Mattis, Charles; Bratcher, Natalie; Burns, Monika; Carosino, Christopher; de Zafra, Christina; Fancher, R. Marcus; Georgi, Katrin; Graff, Candace; Hukkanen, Renee R.; Johnson, Colena; Lao, Yanbin; Lange, Amber; et al.
The IQ Consortium NHP Reuse Working Group (WG) comprises members from 15 pharmaceutical and biotechnology companies. In 2020, the WG developed and distributed a detailed questionnaire on protein non-naïve NHP reuse to the WG member companies. The WG received responses from key stakeholders including principal investigators, facility managers, animal welfare officers and research scientists. This paper's content reflects the consolidated opinion of the WG members and the questionnaire responses on the subject of NHP reuse within nonclinical programs at all stages of research and development. Many of the pharmaceutical companies represented in the working group or participating in the questionnaire have already achieved some level of NHP reuse in their nonclinical programs, but the survey results suggested that there is significant potential to increase NHP reuse further and a need to understand the considerations involved in reuse more clearly. The WG has also focused carefully on the inherent concerns and risks of implementing protein non-naive NHP reuse and has evaluated the best methods of risk assessment and decision-making. This paper presents a discussion on the challenges and opportunities surrounding protein non-naïve NHP reuse and aims to stimulate further industry dialogue on the subject and provide guidance for pharmaceutical companies to establish roadmaps and decision trees enabling increased protein non-naïve NHP reuse. In addition, this paper represents a solid basis for collaborative engagement between pharmaceutical and biotechnology companies with contract research organizations (CROs) to discuss how the availability of protein non-naïve NHP within CROs can be better leveraged for their use within nonclinical studies.